Human mobility and health in a warming world - Schwerdtle, Patricia; Bowen, Kathryn; McMichael, Celia; Sauerborn, Rainer (Journal of travel medicine, 2019)
Climate change will shape patterns of human mobility on a spectrum of voluntary migration to forced displacement. This paper discusses the nexus between climate
Gesehen am 04.07.2019
Submitted 6 December 2018; Revised 17 December 2018; Editorial decision 18 December 2018; Accepted 7 January 2018